Juridical Review of the Implementation of the Fulfillment of Victims' Rights in the Implementation of Diversion in the Juvenile Criminal Justice Process - Syahrul Hidayat; Ahamad Bachtiar; Nazwa Saizidan; Agus Dimyati; Anom Sutrisno (PT Publikasiku Academic Solution, 2025)
In accordance with Law No. 11 of 2012 on the Child Criminal Justice System, Diversion is intended as an alternative approach to handling juvenile criminal cases, aiming to reduce recidivism rates among young offenders in Indonesia. Although the implementation of diversion in the judicial process—at the investigation, prosecution, and trial stages—has proven relatively effective, technical challenges remain, particularly when juvenile offenders deny or default on the terms of diversion agreements. This issue was highlighted in case Number 1/Pid.Sus-Anak/2017/PN.Cbn, where the perpetrator failed to honor the agreement, leading to the re-trial of the case despite the earlier diversion decision. The main objectives of this study are to examine the implementation of diversion in the juvenile justice process according to Law No. 11 of 2012 and to analyze the legal consequences when victims' rights are not fulfilled during diversion. The research uses a normative legal approach, focusing on existing literature and legal frameworks. The findings reveal that if a diversion agreement is not executed within the stipulated time—particularly regarding victim compensation, restoration, or community service—the judge's decision with legal force may be annulled. As demonstrated in the aforementioned case, failure to fulfill diversion terms leads to default, causing the criminal process to resume. This study highlights the need for stricter enforcement of diversion agreements to ensure effective implementation and protection of both the rights of the victims and the integrity of the diversion process.